2017
DOI: 10.1002/ijc.31159
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination with human amniotic epithelial cells confer effective protection in a murine model of Colon adenocarcinoma

Abstract: As a prophylactic cancer vaccine, human amniotic membrane epithelial cells (hAECs) conferred effective protection in a murine model of colon cancer. The immunized mice mounted strong cross-protective CTL and antibody responses. Tumor burden was significantly reduced in tumor-bearing mice after immunization with hAECs. Placental cancer immunotherapy could be a promising approach for primary prevention of cancer. In spite of being the star of therapeutic strategies for cancer treatment, the results of immunother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 46 publications
(83 reference statements)
3
20
0
Order By: Relevance
“…Liver fibrosis, the precursor to cirrhosis, is a complex inflammatory and fibrogenic condition caused by chronic liver injury and an imbalance in extracellular matrix (ECM) synthesis and degradation mediated primarily by activated hepatic stellate cells (HSCs) [146]. hAMSCs and hAMSC-CM were observed to inhibit the activation of HSCs and in turn, to improve liver fibrosis along with reductions of fibrosis markers α-smooth muscle actin (α-SMA), platelet-derived growth factor (PDGF) and collagen I [147,148] and the infiltration of KC cells [149].…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Liver fibrosis, the precursor to cirrhosis, is a complex inflammatory and fibrogenic condition caused by chronic liver injury and an imbalance in extracellular matrix (ECM) synthesis and degradation mediated primarily by activated hepatic stellate cells (HSCs) [146]. hAMSCs and hAMSC-CM were observed to inhibit the activation of HSCs and in turn, to improve liver fibrosis along with reductions of fibrosis markers α-smooth muscle actin (α-SMA), platelet-derived growth factor (PDGF) and collagen I [147,148] and the infiltration of KC cells [149].…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Tabatabaei et al . demonstrated that vaccination using human amniotic epithelial cells induced effective protection against colon adenocarcinoma in a murine model . Other previous studies have also suggested that pluripotent cells share tumor‐specific antigens with cancer cells and may induce antitumor immunity in vivo.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, the application of whole‐cell vaccines provides an alternative in which the vaccine is directed against a broad range of antigens . Immunization with embryonic materials to generate antitumor responses has been developed for some time, but the lack of suitable materials and ethical challenges limits its application . Previous studies have proved that CSC‐based vaccines elicit more effective antitumor responses compared with unselected tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hAECs supress cancers directly by inducing apoptosis and reducing motility of malignant cells (Niknejad et al, 2014). They also suppress tumor development indirectly by promoting anti-tumor cytotoxic T cell immunity in vivo, as shown in a mouse model of colon adenocarcinoma (Tabatabaei et al, 2018).…”
Section: Anti-infection and Anti-cancer Propertiesmentioning
confidence: 95%